2017
DOI: 10.1016/j.dental.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of new natural biomodification agents from Anacardiaceae extracts on dentin collagen cross-linking

Abstract: In conclusion, major components of CNSL yield overall best dentin biomodification outcomes when applied for one minute without staining the dentin collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 34 publications
1
38
0
3
Order By: Relevance
“…3 To overcome these limitations which prevent stable dentin adhesion, there has been an intense search for protocols and techniques that favor bonding with the root dentin. 4,5,6,7,8 The difficulty in achieving a stable hybrid layer with dentin tissue is related to the hydrophilic nature and organic structure of the sealer, 9,10 which can interfere with the sealer-dentin interaction. 11 In fact, incomplete infiltration of resinous monomers into collagen fibers within the hybrid layer favors hydrolysis and degradation of collagen by metalloproteinase (MMP), thus reducing the bonding longevity.…”
Section: Introductionmentioning
confidence: 99%
“…3 To overcome these limitations which prevent stable dentin adhesion, there has been an intense search for protocols and techniques that favor bonding with the root dentin. 4,5,6,7,8 The difficulty in achieving a stable hybrid layer with dentin tissue is related to the hydrophilic nature and organic structure of the sealer, 9,10 which can interfere with the sealer-dentin interaction. 11 In fact, incomplete infiltration of resinous monomers into collagen fibers within the hybrid layer favors hydrolysis and degradation of collagen by metalloproteinase (MMP), thus reducing the bonding longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Além do aumento do ME demonstrado no presente estudo, observa-se uma característica favorável para sua implementação na prática clínica, que é a influência na coloração, que as PAs pigmentam fortemente o substrato 17 , o que não é observado nos grupos usando TA, o que viabiliza o seu uso na odontologia estética, tornando-o bastante promissora a sua aplicabilidade.…”
Section: Discussionunclassified
“…Four dentin bio-modifiers extracted from different plants were compared such as hydrolysable tannins from Aroeira, condensed tannins from grape seed with cardol and cardanol from cashew nut shell liquid. The results demonstrated that the four groups achieved cross-linking in dentin matrix after 1 min of treatment and the best bio-modifiers were cardol and cardanol [78].…”
Section: Dentin Modifier Dentin Pretreatment Collagen Cross-linkingmentioning
confidence: 96%